Perancangan Integrated Environmental Performance Measurement System Di Rumah Sakit - Kurniawan, Chandra; Mubin, Ahmad; Kholik, Heri Mujayin (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Waste has a negative impact on the environment. Hospital medical waste is a hazardous waste for the environment. Environmental performance measurement systems are used to measure the performance of hospitals in handling waste. The measurement of its environmental performance in the hospital is expected to provide improved sewage treatment systems. AHP (Analytical Hierarchy Process) and OMAX (Objactive Matrix) methods are used to design environmental performance systems at hospitals. The data needed is medical and non medical treatment. Data were collected using pairwise comparison questionnaires. The questionnaire data shows the importance of key environmental performance indicators (KEPI). Results of questionnaires processed using Expert Choice. Expert Choice's output produces weight and consistency ratio. Weighted KEPI results are processed by OMAX method. The OMAX method is used to determine the value of environmental performance. There 41 KEPI aspects of the environment. Based on the results of the environmental performance assessment, liquid waste has the highest weight of 0.229.Â